Avaliação multidimensional da qualidade de vida, autoimagem corporal e comportamentos de risco de adolescentes brasileiros - Pinheiro, Bruno De Oliveira [UNIFESP] (2020)
Based on the literature, analyzes and reflections on lifestyles and on the aspects that encourage adolescents to adopt protective or reckless behaviors are necessary so that we can broaden the understanding of the multiple factors involved in quality of life, self-image and health risk behaviors of Brazilian adolescents. The main objective of this study was to assess quality of life, body self-image and health risk behaviors among adolescents; as well as to evaluate the possible association between these factors. The analyzes were based on the responses of 1,081 Brazilian adolescents aged 12 to 19 years old who completed an online questionnaire containing the following instruments: sociodemographic questionnaire, Kidscreen, and Risky Behavior Index (RBI) and Contour Drawing Rating Scale (CDRS). The Jamovi and JASP software, with a 5% significance level, was used to perform descriptive statistical analysis, adjusted logistic regression models, analysis of variance and network analysis. The results were presented in a session containing the raw data and descriptive analyzes regarding the profile of the participating adolescents and in the form of two scientific articles. The main findings of this study presented the definition of the profile of Brazilian adolescents in relation to the quality of life indexes , body self-image and risky behaviors; the evident impact of the socio-cultural context and social experiences on life in adolescents; the bilateral action between the quality of life indexes and risk behaviors in adolescence; the influence of sociodemographic characteristics (gender, age, ethnicity and religion) on the quality of life, body satisfaction and risk behaviors in adolescence and; the impact of variables related to schooling on network analysis (flunk, type of school and level of education). Therefore, this study contributes to the understanding of the impact of multiple subjective variables related to health and present in the lives of Brazilian adolescents.